Meet the Dullards - Pennypacker, Sara 1951-; Salmieri, Daniel 1983- (New York, NY : Balzer + Bray, an imprint of HarperCollinsPublishers, 2015)
"Mr. and Mrs. Dullard move their family to a boring town to avoid any excitment in their lives"--